Synovial chondromatosis combine with synovial tuberculosis of knee joint: a case report - Nan Zhou; Ke Fang; Djandan Tadum Arthur V; Runbin Yi; Feng Xiang; Jie Wen; Sheng Xiao (BMC, 2022)
Abstract Backgroud Synovial chondromatosis is a rare synovial-derived metaplasia disease that comes from the formation of cartilage nodules within the synovial connective tissue of the joint. Knee tuberculosis is a disease caused mostly by the pulmonary tuberculosis and a few by tuberculosis of the digestive tract and lymphatic. tube. Case presentation Herein we report a 3-year-old child admitted by intermittent swelling of left knee joint with lameness for half a year, the patient received surgical treatment. The loose bodies filled in the joint cavity was taken out and the degenerative synovium was excised. Biopsy confirmed as synovial chondromatosis combined with synovial tuberculosis of knee joint. After 6 months follow-ups, knee swelling and claudication get totally recovered and the gait of patient recover back to normal. Conclusion Careful investigation of children with knee pain is recommended to avoid misdiagnosis, Synovial chondromatosis combine with tuberculosis should be considered a differential diagnosis in a child with knee pain.